FACTORES QUE INFLUYEN EN EL ÉXITO DE LA IMPLEMENTACIÓN DE LA TRANSFORMACIÓN DIGITAL - Carlos Arturo Bermúdez Irreño (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Digital transformation is one of the topics that has become more relevant in the organizational environment in recentyears; with the aim of obtaining a higher performance in various aspects and additionally achieve a competitive advantagein the global market. However, confusion has been generated when trying to implement this concept in various organizations,seeing that this phenomenon is more evident in SMEs; therefore, we proceed to make in this article a simple and concretedescription of its meaning, implementation in organizations and in turn an analysis of the factors that have greaterrelevance within its implementation in an organization. The description of the various steps that must be followed to getthe most out of these factors.